Physicochemical Assessment and Water Quality Index of Underground and River Water in Wet Season - Pradhananga-Adhikari, Mandira; Rawal, Narendra Bahadur; Bhatt, Puja; Yadav, Amar Prasad; Adhikari, Nanda Bikram; Joshi, Jarina (Journal of Nepal Biotechnology Association, 2025)
Physicochemical and water quality index (WQI) are the commonly used parameters for evaluating water contamination. Water samples were collected from the Bagmati river (Shankhamul, B-1 and Balkhu, B-2) and well water in the summer season. The physiochemical parameters such as pH, turbidity, dissolved oxygen, oxidation-reduction potential (ORP) and conductivity were measured on the spot and chemical biological parameters such as alkalinity, hardness, chemical oxygen demand (COD) and total coliform colonies were determined in the laboratory. The results showed that well water is less polluted than river water. The contaminants in the river water increased after the confluence of tributaries in the Bagmati river. Although the dissolved oxygen content was low (6.87 ppm), the observed ORP value was higher in the well water (110.1 mV) than in the river water (33.4 mV). The dissolved oxygen content was 7.11 ppm however, the oxidation-reduction potential (ORP) value was negative after the confluence of the tributaries indicating anthropogenic influence. The result is supported by a very high concentration of colonies (20000) observed in the B-2 samples. WQI revealed that the river water quality falls in the ‘C’ grade, indicating poor water quality. It is concluded that the groundwater and river water are polluted hence treatment is essential before using for domestic purposes.